es ce que quelqu'un pourrai m'aider? :s

développer et réduire :

a=(9x-4)(-2x+1)

b= 15x-(2x+5)²

2
a= (9x-4)(-2x+1)
= 18x² +8x+9x-4
b= 15x-(2x+5)²
= 15x-4x²+10x+10x+25
= 4x²+35x+25

Je crois que c'est ça :)
Le deuxième, c'est faux
Ah oui, en effet, mince ..

Réponses

2013-11-02T11:35:01+01:00
a=(9x-4)(-2x+1)
a=-18x²+9x+8x-4
a=-18x²+17x-4
b= 15x-(2x+5)²
b=15x-(4x²+20x+25)
b=15x-4x²-20x-25
b=-4x²-5x-25

2013-11-02T11:43:00+01:00
Bonjour 


a=(9x-4)(-2x+1)
a = -18x² +9x +8x -4
a = -18x² +17x -4

 b= 15x-(2x+5)²

b = 15x - (4x² +20x +25)
b = 15x - 4x² -20x -25
b = -4x² -5x -25